Disorientasi Kekuatan Wanita pada Cerpen Lesung Pipit Karya Eka Kurniawan: Kritik Feminisme - Nasifatul Syarifah; Wika Soviana Devi (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2022)
In society, women often get a share in the domestic field, such as kitchen work, taking care of children, and so on. The position of placing women indicates that women have power under men. In addition, women are also often the target of objectification and subordination by men. As a medium of expression and expression, literature is often a place to criticize all phenomena that occur in society. One of the literary works that shows another strength of a woman is a short story entitled Lesung Pipit by Eka Kurniawan. In this short story, there is a disorientation of power in a woman named Lesung Pipit. In this story, Lesung Pipit is positioned as a woman who obeys the patriarchal culture reflected by her father. However, at the end of the short story it is told that Lesung Pipit took an action to defend his rights as a woman. This story is interesting to study using a feminist critique approach. This is because the short story raises the issue of women and their sexual power. Keywords: disorientasi, kekuatan, wanita, Lesung Pipit.